Boron Oxide B5O6− Cluster as a Boronyl-Based Inorganic Analog of Phenolate Anion - Gao, Shu-Juan; Guo, Jin-Chang; Zhai, Hua-Jin (Frontiers in Chemistry, 2022)
Boron oxide clusters have structural richness and exotic chemical bonding. We report a quantum chemical study on the binary B5O6− cluster, which is relatively oxygen-rich. A global structural search reveals planar C2v (1A1) geometry as the global minimum structure, featuring a heteroatomic hexagonal B3O3 ring as its core. The three unsaturated B sites are terminated by two boronyl (BO) groups and an O− ligand. The B5O6− cluster can be faithfully formulated as B3O3(BO)2O−. This structure is in stark contrast to that of its predecessors, Cs B5O5− and Td B5O4−, both of which have a tetrahedral B center. Thus, there exists a major structural transformation in B5On− series upon oxidation, indicating intriguing competition between tetrahedral and heterocyclic structures. The chemical bonding analyses show weak 6π aromaticity in the B5O6− cluster, rendering it a boronyl analog of phenolate anion (C6H5O−) or boronyl boroxine. The calculated vertical detachment energy of B5O6− cluster is 5.26 eV at PBE0, which greatly surpasses the electron affinities of halogens (Cl: 3.61 eV), suggesting that the cluster belongs to superhalogen anions.